Influences of intergranular structure on the magnetic properties of directly cast nanocrystalline NdFeCoTiNbBC alloys. (6th April 2016) - Zhao, L Z; Hong, Y; Jiao, D L; Qiu, Z G; Zhou, Q; Hussain, M; Liu, Z W; Greneche, J M; Zhang, G Q
Abstract: The millimeter-sized Nd9.5 Fe61.5 Co10 Ti2.5 Nb0.5 B16− x C x ( x   =  0–1.25) alloy rods with various compositions were fabricated by direct casting. Nano-sized hard phase Nd2 (FeCo)14 B, soft phase ɑ -FeCo, and amorphous phase were observed in all alloys. An optimized amount of carbon additions improved the magnetic properties by enhancing the glass forming ability and forming near single domain-sized Nd2 (FeCo)14 B grains around the rod surface. Various intergranular structures were observed in the alloys with x   =  0.25–1. Micromagnetic simulation using the images obtained from the magnetic force microscope and transition electron microscope indicates that the distribution and magnetism of the intergranular phase have an important influence on the magnetic properties and demagnetization process of the alloys. A uniformly distributed nonmagnetic intergranular amorphous phase may enhance the magnetic properties, but the coercivity decreases when the amorphous phase is magnetic. It is important to modify the structure and distribution of the inter-grain amorphous phase in order to achieve high hard magnetic properties in these alloys.